2017
DOI: 10.1161/jaha.117.006242
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardioverter‐Defibrillator Therapy in Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy: Predictors of Appropriate Therapy, Outcomes, and Complications

Abstract: BackgroundArrhythmogenic right ventricular dysplasia/cardiomyopathy is characterized by ventricular arrhythmias and sudden cardiac death. Once the diagnosis is established, risk stratification to determine whether implantable cardioverter‐defibrillator (ICD) placement is warranted is critical.Methods and ResultsThe cohort included 312 patients (163 men, age at presentation 33.6±13.9 years) with definite arrhythmogenic right ventricular dysplasia/cardiomyopathy who received an ICD. Over 8.8±7.33 years, 186 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 26 publications
(113 reference statements)
8
60
0
2
Order By: Relevance
“…The primary outcome was the first appropriate ICD therapy for a VA. Review of intracardiac ECGs or device interrogation interpretation by the referring electrophysiologists when the ECG was unavailable were used to adjudicate arrhythmias, as described previously 13. Decisions regarding implantation and programming of ICDs were made by individual managing electrophysiologists on a case‐by‐case basis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome was the first appropriate ICD therapy for a VA. Review of intracardiac ECGs or device interrogation interpretation by the referring electrophysiologists when the ECG was unavailable were used to adjudicate arrhythmias, as described previously 13. Decisions regarding implantation and programming of ICDs were made by individual managing electrophysiologists on a case‐by‐case basis.…”
Section: Methodsmentioning
confidence: 99%
“…Baseline data included sex, date of birth, date and type of presentation, family history, and results of cardiac testing consisting of 12‐lead ECG, 24‐hour Holter monitoring, 2‐dimensional transthoracic echocardiography, and cardiac magnetic resonance imaging. These covariates were selected based on reported risk factors for VA in ARVC 1, 13, 14, 15, 16. Genotype included the results of sequencing of the desmosomal genes PKP2 (plakophilin 2), DSG2 (desmoglein 2), DSC2 (desmocollin‐2), DSP (desmoplakin), and JUP (plakoglobin) at a minimum.…”
Section: Methodsmentioning
confidence: 99%
“…Among these eight studies, the most recent and largest study reporting the outcomes of ICD therapy in patients with ARVC was published in 2017 41 . This study reported the outcomes of 312 ARVC patients (163 men, age at presentation 33.6±13.9) who received an ICD.…”
Section: Risk Stratification In Patients With Arvcmentioning
confidence: 99%
“…Relatively little is known regarding the outcomes of ARVC patients who have a subcutaneous ICD implanted 41, 44 . Among the 312 ARVC patients described in the recent large report of the outcomes of ICD therapy in ARVC patients, 7 had a subcutaneous ICD implanted 41 .…”
Section: Risk Stratification In Patients With Arvcmentioning
confidence: 99%
“…International guidelines recommend an ICD for secondary prevention in patients with an inherited cardiomyopathy who have suffered a cardiac arrest, and have no serious neurological sequelae or other life limiting illnesses 4344. Use of ICDs for primary prevention in selected patients is supported by several observational studies 41454647. However, in non-ischaemic heart failure, one high quality randomised trial (1116 patients) did not find survival benefit except in a subgroup of younger patients 48.…”
Section: How Are the Inherited Cardiomyopathies Managed?mentioning
confidence: 99%